Junior athroplogist : mobile game based learning apps for children in Sarawak cultural village - Mohamad Sofi, bin Abidin (Universiti Malaysia Sarawak (UNIMAS), 2015)
This paper reports on the development of mobile app (Junior Anthropologist) which is the mobile game based learning apps for children in Sarawak Cultural Village (SCV). The use of this app could possibly enhance the visitors’ experiences at SCV particularly the children. This app could be used for a small group of children too, not limited to one device per children. This could benefit SCV whereby they do not haves to invest on providing the physical devices and eliminate the issues of insufficient information provided to the visitors. With the rapid growth of technologies, the museum and cultural heritage institution especially in Malaysia such as SCV should take this opportunity to give a better services and information to the visitor. This project is one of the opportunities to improve their services and information about SCV.